2008
DOI: 10.1016/j.jnn.2007.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Pacifier stiffness alters the dynamics of the suck central pattern generator

Abstract: Variation in pacifier stiffness on non-nutritive suck (NNS) dynamics was examined among infants born prematurely with a history of respiratory distress syndrome. Three types of silicone pacifiers used in the NICU were tested for stiffness, revealing the Super Soothie â nipple is 7 times stiffer than the Wee Soothie â or Soothie â pacifiers. Suck dynamics among 20 preterm infants were subsequently sampled using the Soothie â and Super Soothie â pacifiers during follow-up at approximately 3-months of age. ANOVA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 34 publications
3
27
0
1
Order By: Relevance
“…30 The results from the present study demonstrate the potent effects of a motorized pacifier nipple on the development of NNS in preterm infants. The patterned orocutaneous experience is physiologically salient and spectrally patterned to resemble the 'burst-pause' structure of the NNS.…”
Section: Discussionsupporting
confidence: 59%
“…30 The results from the present study demonstrate the potent effects of a motorized pacifier nipple on the development of NNS in preterm infants. The patterned orocutaneous experience is physiologically salient and spectrally patterned to resemble the 'burst-pause' structure of the NNS.…”
Section: Discussionsupporting
confidence: 59%
“…A Nellcor OxiMAX N-600X pulse oximeter sensor was placed around each infant's wrist to monitor pulse rate and oxygen saturation (SpO 2 ) throughout the study. Similar to the pacifier preference design described in the work by Zimmerman and Barlow [25], the present protocol consisted of 2-minute suck samples to assess the short-term effects of texture arrays on ororhythmic output. Four suck samples were obtained, including 3 samples with textured silicone pacifiers and 1 sample with a regular Soothie pacifier.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, afferent sensory information is important for error correction in movement or rhythmicity, as well as counteracting any unexpected perturbations in the environment [18, 19]. It has been shown that the sCPG is highly responsive to peripheral input and adapts to changes in task dynamics and local environment, such as volume and consistency of a liquid bolus or mechanical properties of a nipple [21–25]. Sensory flow from the trigeminofacial pathway also modulates the sCPG by tuning the sensitivity of orofacial reflexes [18, 26, 27], with young term infants demonstrating perioral reflex sensitivity to punctate mechanical inputs at a latency of approximately 18–21 milliseconds [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zimmerman and Barlow 4 reported that excessive stiffness may decrease ororhythmic patterning and impact feeding outcome. In addition, previous studies have revealed that there are many differences in variables with regard to feeding or sucking behavior such as perioral movements, 5,6 intraoral (tongue) movements, [7][8][9] intraoral pressure changes, 10-12 the angle of mouth opening 6 and flow rates.…”
Section: Introductionmentioning
confidence: 99%